Strengthening Muslim-Friendly Tourism Attractiveness in Artificial Tourism Destinations in Kota Batu through a 6A's-Based Indicator Development - Siti Nur Inayah; Mochammad Rozikin; Muhammad Shobaruddin (Bulletin of Social Studies and Community Development, 2026)
Muslim-friendly tourism has become a strategic agenda for artificial tourism destinations in Indonesia, including those in Kota Batu, East Java, given the large share of domestic Muslim travelers and Indonesia's position as the country with the largest Muslim population in the world. This study aims to analyze stakeholder understanding of Muslim-friendly tourism, evaluate the readiness of two artificial tourism destinations in Kota Batu, Jatim Park 1 and Alun-alun Kota Batu, identify the strengths, weaknesses, opportunities, and threats affecting their development, and formulate strategies to strengthen their Muslim-friendly tourism attractiveness. A qualitative descriptive approach was used, with primary data collected through in-depth interviews with 15 purposively selected informants across seven stakeholder groups, complemented by structured field observations and document reviews, and analyzed using the interactive model of Milles, Huberman, and Saldana, together with source and method triangulation. Destination readiness was evaluated through six indicators adapted from the 6A’s concept, namely attractions, accessibility, amenities, accommodation, activities, and ancillary services, cross-referenced against the four dimensions of the Global Muslim Travel Index, namely access, communication, environment, and service. Results show that stakeholder understanding of Muslim-friendly tourism remains uneven between government officials and business actors; destination readiness is only partially fulfilled across most components; amenities are relatively strong, while accommodation and ancillary services remain the weakest; and no halal-certified accommodation was found in Kota Batu. A SWOT analysis produced 12 strategic alternatives across the SO, WO, ST, and WT categories, with drafting a regional regulation on Muslim-friendly tourism identified as the priority foundation for implementing the remaining strategies. This study concludes that destination readiness alone is insufficient without a supporting policy framework and contributes a contextual model that links destination management theory to a global tourism readiness standard for developing artificial tourism destinations in Indonesia and comparable contexts. Keywords: Muslim-friendly tourism, 6A's, Global Muslim Travel Index, artificial tourism destination, strategic management.